Investigating products of titanium dissolution in the presence of fluoride ions with dual dynamic voltammetry - Noémi Kovács; Laura Sziráki; Soma Vesztergom; Gyözö G. Láng (Journal of Electrochemical Science and Engineering, 2018)
Products of titanium dissolution in the active state are investigated in fluoride containing 1 M H2SO4 solutions. The novel method of dual dynamic voltammetry, applied to Ti disk/Pt ring rotating ring–disk electrodes, is utilized for the simultaneous detection of different dissolution products. Potential regions where certain products (primarily, TiIII and H2) are formed are identified by a 3D electrochemical map constructed based on the ring–disk electrode measurements. Besides dissolution in the form of TiIII species and hydrogen evolution, the formation and prompt oxidation of TiII can also be presumed under the applied conditions.